The Effects of Tea Polyphenols in Feed on the Immunity, Antioxidant Capacity, and Gut Microbiota of Weaned Goat Kids - Yimei Xiao; Longcheng Chen; Yuewen Xu; Xiaolin He; Shangquan Gan; Fuquan Yin (Animals)
In this present study, we aimed to investigate the effects of adding tea polyphenols to feed on the immunity, antioxidant capacity, and gut microbiota of weaned goat kids. Thirty weaned kids (Leizhou goats, average initial weight of 9.32 ± 1.72 kg, 2 months old) were randomly divided into five groups with six kids in each group, with half being male and half being female. The control (CON) group was fed the basal diet, and the four other groups were supplemented with 2, 4, or 6 g/kg tea polyphenols or 50 mg/kg chlortetracycline in the basal diet (denoted as the T1, T2, T3, and CTC groups, respectively). The results showed that compared to the CON and CTC groups, adding 4 or 6 g/kg tea polyphenols could increase the expression levels of serum antioxidant enzymes and intestinal antioxidant genes in the kids. It also increased the expression of Nrf2 and IL-10 in the intestine, while reducing the content and gene expression of cytokines (IL-1β, IL-6, IFN-γ, and TNF-α). Dietary supplementation with 4 or 6 g/kg tea polyphenols reduced the expression levels of TLR4, MyD88, and NFκB in intestinal tissue, activated intestinal protective mechanisms, and enhanced the immune defense of the intestinal epithelium. Compared to the CTC group, feeding tea polyphenols significantly increased the Simpson indices. However, adding 4 g/kg tea polyphenols significantly increased the relative abundance of Verrucomicrobiota, Candidatus Soleaferrea, the Christensenellaceae R-7 group, and Prevotella, as well as the acetic acid content in the cecum of the kids (p < 0.05). Overall, the results indicate that dietary supplementation with 4 g/kg of tea polyphenols can effectively maintain the homeostasis of the gut microbiota and enhance the anti-inflammatory and antioxidant capabilities of weaned kids.